Impacts of regulatory focus and institutions on innovation. Issue 5 (19th February 2018) - Cowden, Birton J.; Bendickson, Joshua S.
Abstract : Purpose: Many factors influence entrepreneurs, some of which influence the level of innovation (i.e. innovative or imitative) of new products or services pursued. The purpose of this paper is to explore the impact of the psychological motivations of the entrepreneurs and their institutional setting on the innovativeness of the new venture they pursue. Through this exploration, we can gain a better understanding of how innovative new ventures still occur in varying institutional environments. Design/methodology/approach: In order to deliver the authors' propositions as they pertain to innovation, the authors review the literature on entrepreneurs' default regulatory focus (i.e. promotion or prevention seeking) and the strength of the institutions in which they are operating. Findings: The authors theorize that promotion focus enhances innovativeness of ventures while prevention focus enhances imitativeness of ventures. The authors also provide a conceptual framework for the interplay among institutions and regulatory focus and provide a typology for how these varying combinations impact innovativeness or imitativeness of venture type. Originality/value: In this study, the authors discuss and unpack the entrepreneurial mindset in order to bridge gaps between institutions and cognitive motivations of entrepreneurs as they pertain to innovativeness of venture type. By synthesizing several areas of research, the authors shed light on entrepreneurs' innovativeness by proposing how these factors work together in determining whether an entrepreneur's venture is more or less innovative based on regulatory disposition and in different institutional settings.